Cooperation among Wirelessly Connected Static and Mobile Sensor Nodes for Surveillance Applications - Edison Pignaton de Freitas; Tales Heimfarth; Alexey Vinel; Flávio Rech Wagner; Carlos Eduardo Pereira; Tony Larsson (Sensors, 2013)
This paper presents a bio-inspired networking strategy to support the cooperation between static sensors on the ground and mobile sensors in the air to perform surveillance missions in large areas. The goal of the proposal is to provide low overhead in the communication among sensor nodes, while allocating the mobile sensors to perform sensing activities requested by the static ones. Simulations have shown that the strategy is efficient in maintaining low overhead and achieving the desired coordination.